Effect of row spacing on yield performance of sesame mutants - Islam, M S; Rahman, M H; Sarmin, T; Ali, M I; Hossain, M S; Chowdhury, S M A (Bangladesh Journal of Nuclear Agriculture, 2024)
A field experiment was conducted in 2019 to evaluate the effect of row spacing on yield contributing characters of three advanced sesame mutants viz. SM-001, SM-002, SM-003 with one check variety (Binatil-2) at two BINA substation farms, Ishwardi and Chapainawabganj. The experiment was laid out in a RCBD with three replications. Four row spacings viz., 20 cm, 25 cm, 30 cm, and 35 cm were used as treatments. Among different advanced lines/variety, SM-002 produced the highest seed yield (1.07 t ha-1) followed by Binatil-2 (1.05 t ha-1). Among different row spacing, 25 cm showed the highest seed yield (1.11 t ha-1) followed by 30 cm (1.02 t ha-1) with same statistical rank. Between two locations, Chapainawabganj performed better than Ishwardi. The interaction effect between genotype and row spacing revealed that (SM-003) V3 and (Binatil-2) V4 performed best at 20 cm row spacing whereas SM-001 and SM-002 performed best at 25 cm row spacing. The interaction effect of row spacing and location, SM-002 produced the maximum seed yield (1.14 t ha-1) in 25 cm row spacing at Chapainawabganj. The interaction effect of mutants/variety, row spacing, and locations showed that mutant line SM-003 produced maximum seed yield (1.19 t ha-1) at 30 cm row spacing in Chapainawabganj. Bangladesh J. Nuclear Agric, 38(1): 101-109, 2024